Combining vaccines and immune checkpoint inhibitors to prime, expand, and facilitate effective tumor immunotherapy. (3rd August 2018) - Collins, Julie M.; Redman, Jason M.; Gulley, James L.
ABSTRACT: Introduction : Multiple immune checkpoint inhibitors (ICIs) that modulate immune cells in the periphery and the tumor microenvironment (TME) have been approved, as have the therapeutic cancer vaccines sipuleucel-T for metastatic castration-resistant prostate cancer and talimogene laherparepvec (T-VEC) for metastatic melanoma. These developments provide rationale for combining these modalities to improve response rates and durability of responses in a variety of cancers. Preclinical data have shown that vaccines can induce immune responses that turn a tumor from 'cold' to 'hot, ' but vaccines do not appear to be highly active as monotherapy. Areas covered : Here, we provide a review of the current state of vaccine and ICI combination studies. Expert commentary : Most combination trials are in early phases, but several are now in phase III. Vaccines that target antigens expressed exclusively on tumor cells, neoantigens, have the potential to induce robust antitumor responses. Several techniques for predicting which neoepitopes to target, based on tumor mutational profiling, are in various stages of development. To be successful, combination immunotherapy approaches must seek to prime the immune system, expand the immune response, and facilitate immune function within the TME.